2019
DOI: 10.1177/1464420719865292
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the microstructure and mechanical properties of a dissimilar friction stir welded joint of magnesium alloys

Abstract: In the current scenario, the light-weighting concept is the most important strategy to decrease fuel consumption as well as emissions of greenhouse gases. Magnesium alloys are attractive to various industries including transportation industry for their inherent light-weight. The friction stir welding is proficient to join magnesium alloys. In this article, a dissimilar friction stir welding butt joint between AZ31 and AZ61 magnesium alloys was fabricated, and microstructure and mechanical properties have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…This way, FSW joint exhibited lower toughness (about 20%) than base metal. Similar observations have been reported by Singh et al 43 and Ugender et al 54 In contrast, Singh et al 49 reported higher impact toughness of FSW joint than toughness of base metal AZ31B-O Mg alloy. Post welding heat treatment process further reduced the impact toughness of the joint.…”
Section: Impact Toughnesssupporting
confidence: 85%
See 3 more Smart Citations
“…This way, FSW joint exhibited lower toughness (about 20%) than base metal. Similar observations have been reported by Singh et al 43 and Ugender et al 54 In contrast, Singh et al 49 reported higher impact toughness of FSW joint than toughness of base metal AZ31B-O Mg alloy. Post welding heat treatment process further reduced the impact toughness of the joint.…”
Section: Impact Toughnesssupporting
confidence: 85%
“…This is consistent with results reported for aswelded joint in earlier research. 43,50 Failure location of tensile specimens remained unchanged after post welding heat treatment (see Supplemental Figure 5).…”
Section: Tensile Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…To overcome difficulties associated with fusion welding of Mg alloys, Friction Stir Welding (FSW) is the best alternative. 10 FSW process has been used for welding of similar 4,8,10,11 as well as dissimilar Mg alloys, 7,12 Aluminium alloys, 13,14 and Aluminium-Copper.. 15 Friction Stir Welding is a solid-state welding process invented in 1991 by Thomas et al 16 at The Welding Institute (TWI). In FSW, a rotating tool, having predefined geometry, is inserted inside the workpiece material until its shoulder touches the workpiece and allowed to rotate for a definite time period known as dwell time and then moved along the weld joint to produce weldment.…”
Section: Introductionmentioning
confidence: 99%